PERCOBAAN PEMBUNUHAN SEBAGAI PENGHALANG HAK WARIS PERSPEKTIF HUKUM ISLAM DAN KOMPILASI HUKUM ISLAM - Akhmad Khisni; M Ulinnuha (UNISSULA, 2016)
ABSTRACTIn terms of the obstruction of the right of inheritance for the crime of attempted murder of a conflict between Islamic Law and Islamic Law Compilation (KHI). In Islamic law, which was the cause of obstruction of the right of inheritance is someone for murder, slavery, religious differences, and different countries. In conditions that are not elements of the crime of attempted murder as the cause of obstruction of an inheritance. This provision departs from the principle of law in Islamic law regarding jarimah completed the murder and no jarimah / pending (attempted murder).On the other hand, clearly states KHI jarimah attempted murder is the element that causes obstruction of the right of inheritance as a provision contained in Article 173 KHI. Thus visible difference between the provisions of Islamic law and KHI, which has been placed as the provisions of Islamic law for the people of Indonesia. To address the problem, the authors use the research methods of law with juridical-normative legal research conducted by prioritizing research library materials or documents referred to secondary data, in the form of legal materials, primary and secondary. Specifications research is descriptive, which aims to give an overview conducted by way of qualitative theories of law and legal doctrine, and expert opinion of Islamic law.In conclusion, between Islamic law and there is no difference KHI opposite each other with respect to the legal principles adopted by each. The provisions in Article 173 KHI can be filed as a realization of the principles of Islamic law in the delivery of a legal provision will be enforced to have known it, or judge to determine the sentence for the crime ta'zir (jarimah). Conditions resulting known it, or judge it to be established in the form of a regulatory law that was born because of judicial decisions (jurisprudence), which in this case is the provision of an obstruction of the right of inheritance for reasons of criminal offenses of attempted murder.